2022
DOI: 10.1111/mec.16701
|View full text |Cite
|
Sign up to set email alerts
|

Linking pathogen–microbiome–host interactions to explain amphibian population dynamics

Abstract: Symbiosis, defined as living together in physical contact between different species, greatly impacts many aspects of organismal biology. The pervasiveness of these systems in nature led Lynn Margulis to propose that symbiotic interactions are one of the major drivers of evolution (Margulis, 1998). Many characteristics of these associations can vary, including direction of cost/benefit effects, degree of dependence between partners and symbiont transmission traits. This variation profoundly affects ecological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 104 publications
0
12
0
Order By: Relevance
“…There is mixed evidence in the literature of the effects of Bd on genetic diversity, with some studies showing lower genetic diversity in frog populations impacted by Bd (e.g. Byrne et al., 2021; Torres‐Sánchez & Longo, 2022), while others showed stable or even increased genetic diversity in frog populations infected with Bd (e.g. Banks et al., 2020; Horner et al., 2017) including in a microsatellite study of boreal toads from Glacier National Park in Montana (Addis et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There is mixed evidence in the literature of the effects of Bd on genetic diversity, with some studies showing lower genetic diversity in frog populations impacted by Bd (e.g. Byrne et al., 2021; Torres‐Sánchez & Longo, 2022), while others showed stable or even increased genetic diversity in frog populations infected with Bd (e.g. Banks et al., 2020; Horner et al., 2017) including in a microsatellite study of boreal toads from Glacier National Park in Montana (Addis et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Habitat split-related reductions in immunogenetic diversity and changes in MHC class II genotype abundance and expression within populations could covary with microbiome structure and function, as observed in fragmented populations of Ozark hellbenders Cryptobranchus alleganiensis bishopi (Hern andez-G omez, Briggler & Williams, 2018); see also Grieves et al (2021) for a similar correlation between pairwise MHC similarity and preen gland microbiota in birds. Torres-S anchez & Longo (2022) found heterozygote advantage to recruitment of beneficial symbionts, providing defences that increase host fitness. Likewise, microbiome recruitment and natural selection and/or sustained glucocorticoid elevation during development in poor aquatic habitat within a disturbed landscape matrix could affect the development of juvenile skin defences (Hayes, 1995;Knutie et al, 2017b).…”
Section: Potential Mechanisms Linking Habitat Split and Elements Of A...mentioning
confidence: 99%
“…(2021) for a similar correlation between pairwise MHC similarity and preen gland microbiota in birds. Torres‐Sánchez & Longo (2022) found heterozygote advantage to recruitment of beneficial symbionts, providing defences that increase host fitness. Likewise, microbiome recruitment and natural selection and/or sustained glucocorticoid elevation during development in poor aquatic habitat within a disturbed landscape matrix could affect the development of juvenile skin defences (Hayes, 1995; Knutie et al ., 2017 b ).…”
Section: Potential Mechanisms Linking Habitat Split and Elements Of A...mentioning
confidence: 99%
“…Previous studies have shown that genetic distribution of MHC class II alleles was strongly influenced by evolutionary processes such as migration, drift, selection, and demography in amphibians (Cortázar-Chinarro et al, 2017;Luquet et al, 2019). However, very little is known about how evolutionary processes influence skin microbiota diversity in amphibians (Belasen et al, 2021;Torres Sánchez & Longo, 2022). Despite that our results suggested a similar pattern of alpha diversity between regions and populations, the relative abundance of shared ASVs, beta diversity and, thereby, the bacterial community structure composition varied between regions and populations.…”
Section: Microbiome Variation Between Regions and Populationsmentioning
confidence: 99%
“…Among these diseases, chytridiomycosis stands out as an emerging disease caused by the chytrid fungi Batrachochytrium dendrobatidis (Bd) and B. salamandrivorans (Bsal) inflicting amphibian mass die-offs worldwide (Kilpatrick, Briggs, & Daszak, 2010;Martel et al, 2014;Scheele et al, 2019). Recent studies demonstrate the importance of the skin microbiota in amphibian innate immune defense against Bd (Bates et al, 2018;Rebollar et al, 2016;Torres Sánchez & Longo, 2022). Hence, investigating how host MHC genetics, environment and evolutionary history determine the skin microbial diversity and composition of amphibian populations is a priority task in amphibian conservation (Jiménez & Sommer, 2017;Trevelline, Fontaine, Hartup, & Kohl, 2019).…”
Section: Introductionmentioning
confidence: 99%